Citizenship Education in National Character Development - Agnesti, Dea (International Journal of Students Education, 2024)
Education is an effort in various ways so that students are able to develop themselves actively which includes reasoning, intelligence in science, sharpening mentality, having spiritual strength, self-control, and having other skills. Through education, citizens become intelligent, capable, and personable individuals. National character is a characteristic and attitude of a nation that is reflected in the behavior and personality of citizens. The purpose of this study is to shape the character of the nation through civic education (PKn) and to shape the nature of the Indonesian nation. The method used in this study is library research . The results of this study indicate that character education in civics includes the values contained in Pancasila as the main guideline for character education in students with the understanding and implementation of Pancasila values into everyday life as the main foundation of citizen character. Character education also functions to foster potential, habits, and behavior, instill a sense of responsibility and leadership, and create school abilities and environments. By using the literature study research method, which can present a discussion of civic education which is the basis of national character, we can understand the scope of civic education as education based on science as character education that forms the character of citizens according to the nation's culture.